Shrub encroachment accelerates the processes of moisture redistribution in alpine meadows on the Qinghai-Tibetan Plateau - Lirong Zhao; Kexin Li; Ni Zhu; Junmei Gao; Jing Zhang; Di Wang; Xiaoli Wang; Yanlong Wang; Yushou Ma; Yu Liu (Geoderma)
Shrub encroachment in alpine meadows is rapidly occurring under global warming, significantly impacting the regulation of runoff, soil water retention and groundwater conservation. However, the dynamics of soil moisture redistribution following shrub encroachment are poorly understood. Here, the groundwater recharge and water uptake strategies of vegetation were explored through stable water isotope analysis to determine the mechanism of moisture redistribution on the Qinghai-Tibetan Plateau following shrub encroachment. The results indicated that the soil moisture content (SMC) of alpine shrublands (AS) increased significantly compared with that of alpine meadows (AM) and bare lands (BL), which resulted from a decrease in root biomass and an increase in capillary porosity. Furthermore, groundwater recharge from BL and AS was 4.17 and 3.30 times greater than that from AM (12 %), respectively, which was attributed to changes in soil porosity induced by the disappearance of mattic epipedons. In AS, Salix cupularis took up 57 % of the soil moisture from soil depth of 0–10 cm due to high root biomass, and this uptake level was significantly greater than that of Kobresia pygmaea (12 %). Overall, the soil moisture redistribution processes were markedly affected by changes in vegetation and soil parameters under shrub encroachment. These findings suggest that rapid shrub encroachment can accelerate rainfall infiltration and soil moisture dynamics, which can significantly influence hydrological processes on the Qinghai-Tibetan Plateau.